KETERGANTUNGAN KONTEN INSTAN DAN RISIKO POPCORN BRAIN PADA ANAK - M. Fauzan Naufal. S; Munisa; Rizkina Amalia; Kasih Anggraini; Indah Agutin (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
Rapid advancements in digital technology over the past five years have significantly altered information consumption patterns, particularly among children. Easy access to instant content—such as short-form videos and algorithm-driven social media—accustoms children to repetitive, rapid stimulation. This phenomenon has given rise to the term "popcorn brain," describing a state where the brain adapts to constant, high-intensity stimuli, making it difficult to focus on slower activities that require sustained cognitive processing. This article aims to examine the extent of dependency on instant content and the associated risk of "popcorn brain" in children. A literature review methodology was employed. The findings indicate that excessive exposure to instant digital content can reduce attention spans, increase impulsivity, and disrupt children's learning processes. Consequently, the role of parents and educators is crucial in managing digital media usage and encouraging balanced developmental activities.